Analysis of the decision towards the establishment of a robot lab adapted to the century (21) in private schools (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the importance of establishing a robot laboratory compatible withthe challenges of the 21st century, whether in private or government schools. It also aimed toidentify the role of the robot in the educational process and what it provides attractive tools tosimplify the understanding of concepts positively and effectively. The study contained afeasibility study to create a laboratory Robot, and the researcher used the methodology ofdecision analysis through the philosophy of decision-making models (influence charts anddecision tree) within the limits of his knowledge and knowledge.The results of the study showed the following:The theoretical framework for the effectiveness of building a robot laboratory at the schoolwas revealed.• Integration of the robot with education using the modern methods of the 21st century, due tothe attraction of the love of study by students, especially in the elementary stage.• Contributing to the development of positive and recent trends towards the concept of roboteducation in education, and changing negative trends if they exist.In light of these results, the researcher recommended the most important recommendations:1) It is very important to use decision analysis models (decision tree, impact diagrams) forease of use, dealing with alternatives, and reaching the best possible decision.2) Decision trees and influence diagrams complement each other, as they work as one spirit tomake the right, appropriate, and quality decision.3) Influencing schemes and decision trees deal with ambiguity and suspicion, and thisfacilitates the appropriate decision-making process by drawing logical relationships betweenall elements for foresight